2019
DOI: 10.1177/0954409719851626
|View full text |Cite
|
Sign up to set email alerts
|

Bridge transition monitoring: Interpretation of track defects using digital image correlation and distributed fiber optic strain sensing

Abstract: Railway bridge transitions represent locations of vertical stiffness variations that are believed to amplify the dynamic wheel loads which contribute to the development of both differential track settlement and hanging sleeper issues that are difficult to resolve despite the current knowledge of bridge transition behaviour. This paper presents a field monitoring study of a railway bridge transition in which track defects – including both gaps between the rail and sleeper plates, i.e. “rail–sleeper gaps,” and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…The GPS location measurements and car body vertical accelerations were considered in a multiresolution analysis and state machine design methodology for identification of the void zones. A diagnostic of the unsupported sleepers in transition zones using the photogrammetric method is presented in [32][33][34]. The authors of [32] present the results of a field monitoring study of a railway bridge transition with void defects using the measurement of both track displacements using digital image correlation and distributed rail strains using a Rayleigh-based fibre optic analyser.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The GPS location measurements and car body vertical accelerations were considered in a multiresolution analysis and state machine design methodology for identification of the void zones. A diagnostic of the unsupported sleepers in transition zones using the photogrammetric method is presented in [32][33][34]. The authors of [32] present the results of a field monitoring study of a railway bridge transition with void defects using the measurement of both track displacements using digital image correlation and distributed rail strains using a Rayleigh-based fibre optic analyser.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The GPS location measurements and carbody vertical accelerations were considered in a multi-resolution analysis and state machine design methodology for identification of the void zones. A diagnostic of the unsupported sleepers in transition zones using the photogrammetric method is presented in [32,33,34]. The study [32] demonstrates the results of a field monitoring study of a railway bridge transition with void defects using the measurement both track displacements using Digital Image Correlation and distributed rail strains using a Rayleigh-based fibre optic analyser.…”
Section: Review Of the Literaturementioning
confidence: 87%
“…A diagnostic of the unsupported sleepers in transition zones using the photogrammetric method is presented in [32,33,34]. The study [32] demonstrates the results of a field monitoring study of a railway bridge transition with void defects using the measurement both track displacements using Digital Image Correlation and distributed rail strains using a Rayleigh-based fibre optic analyser. The measurements of rail-sleeper gaps are be used to obtain a first-order estimate of the shape of the differential track settlement profile.…”
Section: Review Of the Literaturementioning
confidence: 87%
“…The application of the photogrammetric method for the diagnostic of transition zones is presented in [ 68 , 69 ]. The research [ 68 ] demonstrates the results of a field monitoring study of a railway bridge transition with void defects using the measurement both track displacements using digital image correlation and distributed rail strains using a Rayleigh-based fiber-optic analyzer. It was concluded that measurements of rail–sleeper gaps could be used to obtain a first-order estimate of the shape of the differential track settlement profile.…”
Section: In Situ Measurements Of Rail Deflection In Void Zonementioning
confidence: 99%